Решение уравнение f(x) = g(x), если f(x) = 2x - 1 и g(x)=√(4x+1)

Решение уравнение f(x) = g(x), если f(x) = 2x - 1 и g(x)=√(4x+1)
Гость
Ответ(ы) на вопрос:
Гость
ОДЗ: [latex]4x+1\geqslant0 \Longleftrightarrow x\geqslant-\frac{1}{4}[/latex] [latex]2x-1= \sqrt{4x+1} \Longleftrightarrow \Longleftrightarrow \begin{cases} (2x-1)^{2}=4x+1\\2x-1\geqslant0\end{cases} \Longleftrightarrow \begin{cases} 4x^2-4x+1-4x-1=0\\x\geqslant \frac{1}{2} \end{cases} \Longleftrightarrow \begin{cases}4x(x-2)=0 \\x\geqslant \frac{1}{2} \end{cases}[/latex] [latex]\Longleftrightarrow x=2[/latex].
Не нашли ответ?
Ответить на вопрос
Похожие вопросы